Population Control Through the Family Planning Village Program in Panaikang Village - Tsugiyuki Masunaga; Quanbao Jiang; Fauziah Riska Rahmeina (Journal of Social and Humanities, 2025)
This study aims to determine population control through the Family Planning Village program in Panaikang Village, Sinjai Timur District, Sinjai Regency. This research method uses a qualitative method, meaning that the data collected comes from interview scripts, field notes, and other official documents. The informants in this study were the Family Planning Field Officer (PLKB), the Coordinator of the East Sinjai Family Planning Extension Center, the Head of the East Sinjai Family Planning Cadre, Fertile Age Couples (PUS) who are family planning participants, and Fertile Age Couples (PUS) who are not family planning participants. Using the George C. Edward III policy implementation model. The results of the research conducted according to the data have succeeded in reducing the population birth rate. However, of the four indicators used as a reference, two of them have succeeded, namely the bureaucratic structure and disposition, and two of them are still less successful, namely communication and resources. Where it was found that there was still a lack of socialization of the Family Planning Village program in efforts to control the population through Family Planning (KB) to the community, especially on the part of the husband, so that it became an obstacle in making decisions about family planning.